2012
DOI: 10.1186/2046-4053-1-22
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of brief interventions as part of the screening, brief intervention and referral to treatment (SBIRT) model for reducing the non-medical use of psychoactive substances: a systematic review protocol

Abstract: BackgroundThere is a significant public health burden associated with substance use in Canada. The early detection and/or treatment of risky substance use has the potential to dramatically improve outcomes for those who experience harms from the non-medical use of psychoactive substances, particularly adolescents whose brains are still undergoing development. The Screening, Brief Intervention, and Referral to Treatment model is a comprehensive, integrated approach for the delivery of early intervention and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The database search, which was conducted with assistance from a reference librarian, identified peer‐reviewed studies published in the English language until 26 July 2013 in MEDLINE, PsycINFO and CINAHL Plus (see Supporting information, Table S1 for search keywords). A hand search, which targeted peer‐reviewed papers and grey literature, was conducted by examining references of the included studies, SBIRT bibliographies and several relevant review papers . Authors of the identified studies were e‐mailed, requesting that they provide knowledge of existing studies related to the review.…”
Section: Methodsmentioning
confidence: 99%
“…The database search, which was conducted with assistance from a reference librarian, identified peer‐reviewed studies published in the English language until 26 July 2013 in MEDLINE, PsycINFO and CINAHL Plus (see Supporting information, Table S1 for search keywords). A hand search, which targeted peer‐reviewed papers and grey literature, was conducted by examining references of the included studies, SBIRT bibliographies and several relevant review papers . Authors of the identified studies were e‐mailed, requesting that they provide knowledge of existing studies related to the review.…”
Section: Methodsmentioning
confidence: 99%
“…Delivering brief interventions in emergency departments, primary care and public schools have led to reductions in cannabis use among adolescents [60], and similar findings have also been paralleled among frequent cannabis users [56,61]. There still remains a need for further research on the optimal implementation of the Screening, Brief Intervention and Referral to Treatment framework [62]. Most importantly, the full continuum of this framework needs to be evaluated thoroughly, as opposed to specific components, such as brief interventions or brief treatments [60,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…It has 4 evaluation levels, namely, high (further research is very unlikely to change our confidence in the estimate of effect), moderate (further research is likely to have an important impact on our confidence in the estimate of effect and may change the estimate), low (further research is very likely to have an important impact on our confidence in the estimate of effect and is likely to change the estimate), or very low (very uncertain about the estimate of effect). [ 20 ]…”
Section: Methodsmentioning
confidence: 99%